Treatment of alcohol use disorder in patients with alcohol-associated liver disease: Innovative approaches and a call to action - Lamia Y. Haque; Paola Zuluaga; Robert Muga; Daniel Fuster (Addiction Science & Clinical Practice, 2024)
Abstract Alcohol-associated liver disease is currently the leading cause of liver transplantation and liver deaths both in Europe and the United States. Efficacious treatments exist for alcohol use disorder, but they are seldomly prescribed for patients who need them. Besides, the presence of liver cirrhosis can complicate pharmacological treatment choices. In this review, we discuss established and innovative treatment strategies to treat unhealthy alcohol use in patients with alcohol-associated liver disease. We also describe the experience of our own institutions, Hospital Universitari Germans Trias i Pujol in Badalona (Spain) and Yale-New Haven Health and Yale Medicine (Connecticut. United States of America).